(untitled) (Historia, 2021)
In this, his last book, the late Jeffrey Butler explores the fundamental socio-economic dynamics that moulded the physical nature of South African communities. The political arsenal of governments from the period of segregation and apartheid wielded influences on the development of communities and every aspect of the citizenry. The existence and nature of many townships such as Sowcto, Sharpcville and others were shaped by social engineering endeavours implemented by the apartheid regime. The housing structures built by the apartheid government in townships arc an indication of the survival of symbols associated with the contestation of memory, place and identity. Robust deliberations on the history and development of townships, although somewhat onerous because of its plural content base, require intellectual rigour and stamina. Nevertheless, the development of townships has received much attention from scholars in an attempt to gain a better understanding of processes that shape communities, towns, and urban centres.